Immunotopographical Differences of Human Skin - Béke, Gabriella; Dajnoki, Zsolt; Kapitány, Anikó; Gáspár, Krisztián; Medgyesi, Barbara; Póliska, Szilárd; Hendrik, Zoltán; Péter, Zoltán; Törőcsik, Dániel; Bíró, Tamás; Szegedi, Andrea (Frontiers in Immunology, 2018)
The immunological barrier of the healthy skin is considered to be unified on the whole body surface – however, recent indirect findings have challenged this dogma since microbial and chemical milieu (e.g. sebum, sweat, pH) exhibit remarkable differences on topographically distinct skin areas. Therefore, in the present study, we performed whole transcriptomic and subsequent pathway analyses to assess differences between sebaceous gland rich (SGR) and sebaceous gland poor (SGP) regions. Here, we provide the first evidence that different skin regions exhibit a characteristic innate and adaptive immune and barrier milieu as we could detect significantly increased chemokine (CCL2, 3, 19, 20, 23, 24) and antimicrobial peptide (S100A7, A8, A9, lipocalin, β-defensin-2) expression, altered barrier (keratin 17, 79) functions and a non-inflammatory Th17/IL-17 dominance in SGR skin compared to SGP. Regarding pro-inflammatory molecules (IL-1α, IL-6, IL-8, IL-33, TNF-α), similarly low levels were detected in both regions. Our data may explain the characteristic topographical localization of some immune-mediated and autoimmune skin disorders and we also propose that the term „healthy skin control sample”, widely used in experimental Dermatology, should only be accepted if researchers carefully specify the exact region of the healthy skin (along with the site of the diseased sample).